THOMAS STAMFORD RAFFLES: SEORANG UNIVERSALIS ATAU IMPERIALIS? - Hariyono, Hariyono; Wijaya, Daya Negri (Paramita: Historical Studies Journal, 2016)
It is debatable that Raffles is seemed to be a Universalist or an imperialist. The first refers to a belief that he is an agent of the spread of Western values to the Eastern. Others claim that he is the Western imperialist to the Eastern. This is caused by the forced values to the Eastern. Raffles issued the reformation of policy because the colonialism of VOC and the government of French-Dutch did not have any humanistic policy. He issued many humanistic policies till the end of his government in Java. One of his policies was the slavery tax. The tax was used specifically to abolish the practice of slavery and to the welfare of people. In other side, Raffles forced people to work in his friendâs land, Alexander Hare who opened the plantation in Banjarmasin. The life of workers was really suffering however his thoughts and his efforts becoming an insight to oppose the heritage of feudalism (slavery). To short, there was a lesson learnt why Rafflesâ ideas were failed and came back to the previous structure.Â Â Raffles dalam satu sisi terlihat sebagai seorang universalis dan disisi lain sebagai seorang imperialis. Ada yang memandang Raffles di Nusantara adalah penyebar nilai-nilai Barat ke dunia Timur. Sejarawan lain memandang Raffles sebagai bagian dari imperialisme Barat ke dunia Timur karena nilai-nilai yang ditawarkan tidak cocok dan dipaksakan secara politis. Raffles melakukan reformasi kebijakan karena kolonialisme VOC dan pemerintah kolonial Prancis-Belanda dirasa tidak humanis. Dia mengeluarkan banyak kebijakan yang bersifat humanis hingga akhir kepemimpinan. Salah satu kebijakannya adalah memberlakukan pajak bagi rakyat yang memiliki budak. Pajak digunakan sebagai penghapus praktek perbudakan secara khusus dan untuk kemaslahatan umat secara umum. Pada sisi lain Raffles mengirim pekerja pada sahabatnya Alexander Hare yang membuka perkebunan di dekat Banjarmasin. Kehidupan pekerja disana tentu sangat menderita tetapi pemikiran dan usahanya menjadi pelopor dalam menentang warisan feodalisme (perbudakan) yang patut dicela. Setidaknya dapat dijadikan pelajaran mengapa ide Raffles akhirnya terbentur dan kembali pada tatanan sebelumnya.Â